PENERAPAN BUDAYA 5S DALAM MENINGKATKAN MUTU PENDIDIKAN KARAKTER SISWA SMP NEGERI 3 POLOKARTO - Devita Dwi Ramawati; Yeyen Syafitri; Yogi Arga Jalu Pratama; Atiqa Sabardila; Main Sufanti (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The implementation of 5S culture in improving the quality of student character education at SMP Negeri 3 Polokarto. The formulation of the problems contained in this article is, How to planning 5S activities at Smpn 3 polokarto, How to implement 5S Activities at SMPN 3 polokarto, How to realize 5S movement activities in improving character education student at SMPN 3 polokarto this study aims to determine how important 5S culture is in cultivating character in students of smp negeri 3 polokarto. This research uses qualitative methods, a method which can be interpreted as a research activity that prioritizes combined data obtained from field research and is manifested in the form of words,phrases,clauses,sentences,discourses.Based on the results obtained from observations, 5S cultural activities can improve student character education, students are taught to be polite and courteous to anyone, students are also taught to smile, greet and greet every time they meet or meet friends or teachers,and students can know and practice how culture of the 5S.